Have U.S. - Japan Trade Agreements Made a Difference? - Gangnes, Byron (Institutional Knowledge at Singapore Management University, 2004)
International trade is governed by a complicated patchwork of international treaties, bilateral agreements, and unilateral actions, often directed at trade in very specific commodities. A determination of the impact of trade measures begins with an assessment of their direct effect on trade volumes and prices in targeted sectors. While in some cases—such as the recent U.S. anti-dumping duties on steel—the measures have readily identifiable impacts, in others cases the effects are more difficult to determine.